2015
DOI: 10.2105/ajph.2015.302851
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mammography Screening Guidelines Among Transgender Persons and Sexual Minority Women

Abstract: We used retrospective (2012-2013) chart review to examine breast cancer screening among transgender persons and sexual minority women (n = 1263) attending an urban community health center in Massachusetts. Transgender were less likely than cisgender patients and bisexuals were less likely than heterosexuals and lesbians to adhere to mammography screening guidelines (respectively, adjusted odds ratios = 0.53 and 0.56; 95% confidence intervals = 0.31, 0.91 and 0.34, 0.92) after adjustment for sociodemographics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 15 publications
2
38
0
3
Order By: Relevance
“…Yet, the use of mammography in transgender individuals has not been adequately studied. Importantly, one retrospective study of transgender individuals at a community health center in Massachusetts showed that transgender individuals were not as likely as cisgender patients to follow guidelines of mammography screening [16]. Maglione et al analyzed 8 existing cases and described two original cases (65-year-old and a 55-year-old that had a family history of breast cancer) of MtF transgender individuals who developed breast cancer, reporting that breast cancer occurs at a younger age and is more often ER (estrogen receptor) positive compared to males [5].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the use of mammography in transgender individuals has not been adequately studied. Importantly, one retrospective study of transgender individuals at a community health center in Massachusetts showed that transgender individuals were not as likely as cisgender patients to follow guidelines of mammography screening [16]. Maglione et al analyzed 8 existing cases and described two original cases (65-year-old and a 55-year-old that had a family history of breast cancer) of MtF transgender individuals who developed breast cancer, reporting that breast cancer occurs at a younger age and is more often ER (estrogen receptor) positive compared to males [5].…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation of medical records from a community health center that provides care to underserved populations, including gender and sexual minorities, examined adherence to mammography screening guidelines. Adherence was defined as having 1 or more mammograms during the preceding 2-year interval (109). Among nontransgender females included in the study, 73% were considered screening adherent.…”
Section: Other Cancer Risk Factorsmentioning
confidence: 99%
“…5458 Extant literature demonstrates that sexual minority women underutilize cervical cancer screening services. Screening rates are estimated to be between 43 – 71% compared to 73% in the general female population.…”
Section: Disparities In Unmet Medical Needs By Sexual Orientationmentioning
confidence: 99%